PENGGUNAAN ALAT PERAGA DALAM PEMBELAJARAN - Dahniar (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2020)
Teaching aids is a tool or equipment used by teachers when communicating in the teaching and learning process. Teaching aids include all learning resources that can be used in the teaching and learning process so that teaching can take place well, draw closer or smooth the road to the planned goals. All types of teaching aids that can channel messages, stimulate the mind, attention, and facilitate student understanding of the material being taught, then all of them can be used as props in increasing student understanding of both objects and their surroundings. Teaching aids is a tool or equipment used by teachers when communicating in the teaching and learning process. Teaching aids include all learning resources that can be used in the teaching and learning process so that teaching can take place well, draw closer or smooth the road to the planned goals. All types of teaching aids that can channel messages, stimulate the mind, attention, and facilitate student understanding of the material being taught, then all of them can be used as props in increasing student understanding of both objects and their surroundings